Individual predictors of autonomous vehicle public acceptance and intention to use: A systematic review of the literature - Fahimeh Golbabaei; Tan Yigitcanlar; Alexander Paz; Jonathan Bunker (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
Fully autonomous vehicles (AV) would potentially be one of the most disruptive technologies of our time. The extent of the prospective benefits of AVs is strongly linked to how widely they will be accepted and adopted. Monitoring and tracking of individuals' reactions and intentions to use AVs are critical. The current study aims to explore and classify individual predictors (i.e., influential factors or determinants) of public acceptance of, and intention to use AVs, by conducting a systematic literature review and developing a conceptual framework to map out the individual influential factors that shape public attitudes towards AVs, which influence user acceptance and adoption preferences. This framework contains the key factors identified in the systematic review-i.e., demographic, psychological, and mobility behavior characteristics. The findings of the review disclose that public perceptions and adoption intentions vary significantly among different socio-demographic cohorts. Commuters value different aspects concerning AVs, which shape their intentions on acceptance and adoption. Thus, direct experience with AVs along with education and communication would be helpful to change people's attitudes towards AVs in a positive way. The study informs urban and transport policymakers, managers, and planners, and helps in planning for a healthy AV adoption process with minimal societal disruption.
Keywords: 650; autonomous vehicles; autonomous driving; autonomous vehicle adoption decisions; public attitudes toward autonomous vehicles; intention to use autonomous vehicles; user acceptance of autonomous vehicles; mobility behavior; urban mobility; mobility innovation